Research into advertising in construction: Analysis of Lithuanian and Swedish experience - Banaitis, Audrius; Banaitiene, Nerija (Technological and Economic Development of Economy, 2005)
Construction, as an object of marketing, has special features: the construction environment is complex and changing, clients’ requirements and expectations are increasing. Construction companies must realize that good marketing, as well as advertising activities have a great impact on sales of construction products and services in today's competitive market. This paper reports on a qualitative study of the Lithuanian and Swedish construction companies about advertising campaign, budget and means of advertising. The effectiveness of advertising means is also analyzed. The first problem identified in the study is that most Lithuanian construction companies provide self‐advertising policy. The lack of experience and knowledge of advertising leads organizations to inadequate decisions. The observations also detected that advertising campaign in the Lithuanian construction companies is underfinanced and the advertising budget is closely linked with used means. The paper concludes with the assessment of the study results and directions for further research.Reklamos statyboje tyrimas: Lietuvos ir Švedijos įmonių patirties analizėSantrauka. Statyba, kaip marketingo objektas, turi tam tikrų ypatybių: statybos aplinka yra kompleksinė ir kintama, klientų reikalavimai ir lūkesčiai nuolat auga. Statybos įmonės turi suprasti, kad geras marketingas ir ypač reklama turi didelę įtaką statybos produktų ir paslaugu pardavimams, o tai ypač svarbu šiandienines rinkos sąlygomis. Straipsnyje pateikiamas Lietuvos ir Švedijos statybos įmonių kokybinis tyrimas, kuriame nagrinėjami reklamos kampanijos, biudžeto ir nešiklių klausimai. Nagrinėjami ir reklamos efektyvumo įvertinimo klausimai. Tyrimas parodė, kad daugelis Lietuvos statybos įmonių reklamuojasi savo jėgomis. Kadangi įmonių darbuotojai neturi reklamos organizavimo patirties ir žinių, jie dažnai priima netinkamus sprendimus. Lietuvos statybos įmonių tyrimas parodė, kad įmonės neskiria pakankamai lėšų įmonės produktų ar paslaugų reklamai, ir reklamos biudžetas yra glaudžiai susijęs su pasirinktais reklamos nešikliais. Straipsnio pabaigoje aptariami tyrimo rezultatai ir pateikiami siūlymai statybos įmonių reklamai organizuoti.Reikšminiai žodžiai: reklama, statybos įmonė, reklamos nešikliai, reklamos kampanija, tyrimas.First Published Online: 21 Oct 2010